PERSEPSI MAHASISWA TERHADAP KUALITAS WEBSITE GEOPARK : KASUS PADA GEOPARK BATUR - Yuliawati, Ayu Krishna; Budiman, Arief; Wulung, Shandra Rama Panji; Aryanti, Asti Nur (IMAGE : Jurnal Riset Manajemen, 2018)
Geopark Global Geopark Batur as a geopark is not as well known as other geoparks in the world. Promotional efforts are carried out using the geopark website. The purpose of this study is to obtain the perception of students on Batur Global Geopark’s website quality. The research method used is qualitative and respondents are students at UPI management study program. The results shows Batur Global Geopark website quality is quite good according to the respondents and able to attract several new customer and increase knowledge about geopark as a tourism destination.